Diffuse Alveolar Hemorrhage Induced by Vaping - Michael Agustin; Michele Yamamoto; Felix Cabrera; Ricardo Eusebio (Case Reports in Pulmonology)
There has been a significant increase in electronic cigarette (e-cigarette) use since its introduction in 2007. Ironically, there remains very few published literature on the respiratory complications of e-cigarettes. The use of personalized vaporizers or commonly known as “vaping” has started to overtake standard e-cigarette. Its dynamic vaporizer customization makes it challenging to assess long-term health effects. Case reports on the pulmonary complications of e-cigarettes are limited to bronchiectasis, eosinophilic pneumonia, pleural effusion, and suspected hypersensitivity pneumonitis. Diffuse alveolar hemorrhage (DAH) is bleeding into the alveolar spaces of the lung secondary to disruption of the alveolar-capillary basement membrane. We report a case of young male presenting with subacute respiratory failure. He was later found to have diffuse alveolar hemorrhage syndrome that is likely induced by aggressive vaping. This adds up to the rising concern on the possible serious complications of this innovative technology designed as a safer alternative to traditional cigarettes.